Developing Business Resilience Strategy For PT Nusantara Totalindo Logistik - Pratama, Rizky Anugrah; Harianto; Taryana, Asep (School of Business, IPB University (SB-IPB), 2023)
T Nusantara Totalindo Logistik is a business that operates in the freight forwarding sector with rapid progress, but they are facing introduction and turbulences. To meet both occurrences, they need business resilience strategies. The Business Resilience Strategy was realized to identify PT NTL's business potential and advantages and build business resilience for PT NTL through creating a vision and mission statement until risk management. This research aims to develop resiliency over PT NTL business to enhance business potential and realize a business resilience strategy by establishing a vision and mission for business risk management. The research data and methodological approach for this research came from interviews and questionnaires regarding risk management and creating business resilience strategy through vision and mission statement until risk management by identifying vulnerability factors and capability factors, designing work programs and risk management, IFE Analysis, EFE Analysis, VRIO Analysis, TOWS Strategy Matrix, work program and creating risk management. Based on the research result, we can conclude that a business resilience strategy starts from assembling a vision and mission statement to risk management. The managerial implications of a business resilience strategy are establishing the strategy up to risk management. Keywords: risk management, business resilience, business potential, risk, Nusantara Totalindo